Stokes' second problem for rotating MHD flow of a maxwell fluid in a porous medium - Khan, Ilyas (2014)
An analysis is presented to establish the exact solution of Stokes' second problem for magnetohydrodynamic (MHD) rotating flows of Maxwell fluid in a porous medium. Based on modified Darcy's law the expressions for dimensionless velocity are obtained by using Laplace transform method. The derived steady and transient solutions satisfying the involved differential equations and imposed boundary and initial conditions. The influence of various parameters on the velocity has been analyzed in graphs and discussed.